Development of a risk-based Combustion Toxicity Index for engineering materials. (3rd September 2010) - John, Siby; Chander, Mahesh
The various types of modern materials widely used in engineering works possess high risk of combustion. During combustion of these materials, toxic gases of varying concentrations are generated. Inhalation of toxic combustion products is the major cause of death during fires. Increased knowledge of the combustion products and their toxicity could decrease the risks. This paper describes the development and validation of a Combustion Toxicity Index (CTI) that can be used to compare the toxicity risk of engineering materials on combustion. Quantitatively, the results were in good agreement with literature data. However, the application of the CTI is limited to a relative ranking system for comparison of toxicity risk of engineering materials.